اُمت مسلمہ کی دعوتی ذمہ داریاں تفسیر ضیاء القرآن کی روشنی میں: Invitational responsibilities of the Muslim Ummah in the light of Tafsir Zia-ul-Quran - Noor Hussain (MEI, 2023)
The propagation of Islam depends on preaching and preaching only۔ Therefore, Allah Almighty Himself taught Holy Prophet (SAW) the etiquette of Islamic Da'wah.After the demise of the Messenger of Allah the responsibility of da'wah and preaching is now the responsibility of the Muslim Ummah till the Day of Judgment.Per Muhammad Karam Shah Al-Azhari has a prominent position as a renowned and serious scholar. They are respected in all School of thoughts.Pir Karam Shah Al-Azhari dedicated his life to Da'wah of Islam.Like a true da'i, he have adopted all the methods that are the obligatory syllabus of the da'i of Islam.His Tafsir Zia-ul-Quran has a special place in terms of its characteristics.Among other features of Tafsir Zia-ul-Quran, the most important feature is the da'wah discussions and articles۔If the Muslim Ummah keep in mind the writing style of Tafsir Zia-ul-Quran, then surely they can do the work of Da'wah more effectively. In the following article, Invitational responsibilities of the Muslim Ummah in the light of Tafsir Zia-ul-Quran will be highlighted.